Quorum Based Conflict Resolution Algorithms In Distributed Systems - Armin Lawi (Department of Mathematics, Hasanuddin University, 2005)
Mutual exclusion is one of the most fundamental issues in the study of distributed systems. The problem arises when two or more processes are competing to use a mutual exclusive resource concurrently, i.e., the resource can only be used by at most one process at a time. Synchronizations adopting quorum systems are an important class of distributed algorithms since they are gracefully and significantly tolerate process and communication failures that may lead to network partitioning. Coterie based algorithm is a typical quorum based algorithm for mutual exclusion: A process can use the resource only if it obtains permissions from all processes in any quorum ofcoterie, and since each quorum intersects with each other and each process only issues one permission, the mutual exclusion can be guaranteed. Many quorum systems have been defined based on the relaxation of the properties of coterie system. Each of them is designed to resolve its corresponding problem, e.g., k-coterie based algorithm to resolve the k-mutual exclusion, local coterie for the generalized mutual exclusion, (h, k)-arbiter for h-out of-k resource allocation problem, etc. Therefore, design an algorithm for any distributed conflict resolution problem is only meant to define a new quorum system which can be implemented to the corresponding problem. Since most of distributed conflict resolution problems are designed based on the relaxation of the safety property of mutual exclusion, understanding the way to relaxing the safety property and its quorum system is important to study any kind of conflict resolution problem in distributed systems.